Les transformateurs Duchamp - Lyotard, Jean-François; Judovitz, Dalia; Parret, Herman; McLeod, Ian (Leuven : Leuven University Press, 2010)
This book is the third of a series of five volumes that exhaustively brings together the writings of Jean-François Lyotard (1924-1998) on contemporary art and artists. This collection of essays, written between 1974 and 1977 in the middle of the time of Duchamp's rediscovery in France, was published by Editions Galilée (Paris) in 1977 and in English translation by The Lapis Press (Los Angeles) in 1990. This volume republishes the two versions face to face, including the drawings, diagrams and images of the original edition. Herman Parret presents the text in a substantial introduction and Dalia Judovitz situates it in the more general framework of Lyotardian philosophical reflection. Duchamp's 'TRANS/formers' reconstructs the 'Large glass and given', Duchamp's two major works that glorify the body in its topological conceptuality.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Lyotard, Jean-François; Duchamp, Marcel